Puberdade e maturidade sexual de ovinos portadores da genética FecGE - Pereira, Clêrton Magno Rocha Santana (2018)
Identified on Santa Ines sheep breed with history of multiple parturitions, the mutation FecGE of the growth and diferentiation factor -9 gene (GDF-9), causes an increase in the ovulation rate and in prolificacy. Although, associations of GDF-9 with the reproductive physiology of males are not totally clarified and there are no studies which relate this gene and neither FecGE with the reproductive development of sheep, controled by hormonal mechanisms, influenced by genetic factores and that suffers interference from environmental and nutritional factors. The sexual puberty and maturity characterization of FecGE lambs, besides contribuing for the knowlodge of this mutation effects over reprodcutive physiology and male sexual development, may enable the usage of this animals on the selection and genetic improvement of sheep. The main objective of this work was to study and measure the effects of the FecGE mutation on the reproductive physiology of Santa Ines lambs, focusing on its sexual development. Thirty-six lambs genotyped for FecGE were used and distributed according to their genotype: homozygous non mutante and, heterozygous and homozygous mutants. Every 15 days through 11 months, the lambs were evaluated andrologically (scrotal circumference; seminal volume; sperm concentration, motility and viability; spermatic vigor and sperm with major, minor and total defects) to verify the influence of this mutation over physiology and puberty and sexual maturity ages. The data were submitted to covariance analysis with measures repeated in time, considering the birth weigh as covariable. Differences between the genotypes were not observed in this study. The FecGE mutation did not influence the parameters over the experimental period and over the puberty (187,87 ± 6,54 days) and the sexual maturity (230,31 ± 9,87 days) ages. This work allowed to be verified for the first time the effects of FecGE on the males reproductive physiology , concluding that this mutations does not have influence on andrological, seminal and spermatic parameters and neither on puberty and sexual maturity ages of Santa Inês lambs, whom can be used as breeding disseminators of this prolific genetics.